2021
DOI: 10.5603/rpor.a2021.0126
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of red cell distribution width (RDW), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR) in radiotherapy for oropharyngeal cancer

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 26 publications
1
14
0
2
Order By: Relevance
“…Several studies, including a meta‐analysis, have reported the prognostic utility of the NLR, LMR, PLR, PNI, and HS‐mGPS in head and neck cancers 9–20,22–29 . Regarding previous reports on a systematic review and meta‐analysis, Yang et al 22 investigated a total of 25 studies and demonstrated that higher pretreatment NLR was associated with poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies, including a meta‐analysis, have reported the prognostic utility of the NLR, LMR, PLR, PNI, and HS‐mGPS in head and neck cancers 9–20,22–29 . Regarding previous reports on a systematic review and meta‐analysis, Yang et al 22 investigated a total of 25 studies and demonstrated that higher pretreatment NLR was associated with poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, including a meta‐analysis, have reported the prognostic utility of the NLR, LMR, PLR, PNI, and HS‐mGPS in head and neck cancers. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 Regarding previous reports on a systematic review and meta‐analysis, Yang et al 22 investigated a total of 25 studies and demonstrated that higher pretreatment NLR was associated with poorer prognosis. Takenaka et al 23 reviewed 19 studies of head and neck cancer and showed that an elevated pretreatment NLR had a predictive value of poorer OS and DSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Benzer şekilde diğer çalışmalarda da orofarinks kanseri ve küçük hücreli dışı akciğer kanserlerinde NLR'nin sağkalım için bağımsız bir öngörücü olduğu bulunmuştur. 4,5 Çalışmamızda literatür ile uyumlu olarak pnömoninin şiddeti arttıkça NLR'de anlamlı bir yükselme olduğu, NLR yükseldikçe yoğun bakım yatış riskinin anlamlı şekilde arttığı görüldü. Fakat literatürden farklı olarak pnömoninin şiddeti arttıkça PLR değerinde anlamlı bir değişiklik olmadığı saptandı.…”
Section: Rdw Nlr Hrr Ve Crp Değerleri Arasındaki Ilişkiyi Belirlemek ...unclassified
“…3 Özellikle küçük hücreli dışı akciğer kanserlerinin ve üst solunum yolu kanserlerinin prognozunu tahmin etmedeki başarısı yapılan çalışmalarda görülmüştür. 4,5 Platelet/lenfosit oranı [platelet/lymphocyte ratio (PLR)], pnömoni gibi bulaşıcı hastalıkların şiddetini belirleyebilir ve vücuttaki inflamatuar yanıtın ve vasküler trombozun derecesini yansıtabilir. 6 Eritrosit dağılım genişliği [red cell distribution width (RDW)], dolaşım sistemindeki eritrosit hacminin varyasyon katsayısıdır.…”
unclassified